Contemporary Malaysian art: the integration of Islamic values in new trends and approaches since 1980 / Muhammad Faiz Sabri - Sabri, Muhammad Faiz (2020)
Contemporary Islamic art has been recognized and was developed within the Malay culture since the 13th century, where the Malay society formalized their culture based on Islamic concepts and teachings. The years between 1980 and 1990 can be considered as a revival period of Islamic art in Malaysia and became one of the main significant art forms in the development of modern art at that time. However, in the 20th century, modern global influences have given a ‘new meaning’ to contemporary Islamic art in Malaysia. The Islamic Malay Cultural spirits have slowly missed their place in society. Therefore, this research was conducted to understand in depth the view of contemporary Islamic art in Malaysia from the year 1980 to the present by analyzing the concepts and philosophies of Islam applied specifically in contemporary Islamic artwork. This research was employed a qualitative type of research as a method, and the significance of this research is the model developed, which refers to the case study as introduced by Creswell (2017). Over 196 samples of contemporary Islamic artworks were collected based on five prominent Islamic art exhibitions namely Pameran Seni Lukis & Seni Khat (1984), Identiti Islam dalam Seni Rupa Malaysia: Pencapaian dan Cabaran (1992), Manifestasi Jiwa Islam dalam Seni Rupa Malaysia (1993), Art and Sprirituality (1995), and Kesenian Islam: Suatu Perspektif Malaysia (1995) and it has analyzed based on the four steps of art criticism introduced by Edmund Feldman (1994), which consists of description, analysis, interpretation and judgment. In defining certain Islamic concepts in selected artworks, this research was referring to the principles of Islamic design introduced by Ismail Al- Faruqi, which consist of abstraction, non-individualization, intricacy, successive combination and repetition. The selection of the sample was based on the Islamic art theme, which specifically focusing on a group of prominent Islamic art exhibitions that were exhibited during a few decades. Apart from that, in order to support the understanding of the view of contemporary Islamic art in Malaysia, the interview session with Islamic art experts and academics were conducted and transcribed to see their opinions and perceptions regarding the topic covered. This action was taken in conjunction to enhance the understanding of the findings of this research. Consequently, the analysis and findings of this research showed that the selection of the samples was classified into four disciplines of art, namely painting, sculpture, printmaking, and mixed media, as these forms of art still recognized and show it’s relevancy in Malaysian art scene nowadays. On top of that, the findings of this research also found that the main strategy that frequently used by Malaysian artists in producing contemporary Islamic artworks are according to the five principles which have introduced by Ismail al-Faruqi that consists of abstraction, non-individualization, intricacy, successive combination and repetition. It is hoped that this research will contribute toward enhancing the view of contemporary Islamic art specifically after the year of 1980, thus guiding contemporary Muslim artists to appreciate and understand contemporary Islamic art well. Finally, it is hoped to stimulate a potential emerging artist to create new expressions of contemporary and innovative artworks while at the same time remaining true Islamic spirit.